2013
DOI: 10.1007/s00066-013-0358-6
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional surface scanning for accurate patient positioning and monitoring during breast cancer radiotherapy

Abstract: Optical surface scanning is a simple, fast and reproducible method for breast cancer patient alignment. Particularly for more sophisticated irradiation techniques, it helps to improve accuracy in patient positioning during radiotherapy without the exposure to additional ionizing radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…Intrafraction motion is mainly due to breathing movements but also to relaxation of the patient during the session 38. It was confirmed by our own experience with surface‐based repositioning system.…”
Section: Discussionsupporting
confidence: 62%
“…Intrafraction motion is mainly due to breathing movements but also to relaxation of the patient during the session 38. It was confirmed by our own experience with surface‐based repositioning system.…”
Section: Discussionsupporting
confidence: 62%
“…A combination of EMT with surface imaging could improve the registration and also be sensitive to potential non‐rigid inter‐fractional changes of the patient's anatomy, for example, changes in breast posture. Various surface imaging systems are available mainly for patient positioning in external beam radiation therapy 33, 34, 35. CT‐extracted surfaces could be used as a reference such that daily measured patient surfaces in combination with, for example, IR‐reflective fiducials on the EMT‐fiducial sensors would allow a registration of EMT and CT‐surface on a daily level.…”
Section: Discussionmentioning
confidence: 99%
“…Recent patient studies showed similar accuracy errors in OSI patient setup, suggesting the OSI should be carefully used because of the relatively large interfraction variability. [13][14][15][16] According to the study of Betgen et al, 13 interfraction systematic and random errors are 2.0-5.0 mm and 0.9-2.2 mm for translation and between 0.08…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on the OSI accuracy using patients can be found in Refs. [13][14][15][16], which argue OSI may reduce CBCT scan frequency for patient setup where tumor location is fixed relative to the surface although interfraction error is relatively large. Here, we evaluate the accuracy of surface registration by comparing registration results with that of a conventional volumetric registration method for 26 head-and-neck cases based on simulation experiments.…”
Section: Introductionmentioning
confidence: 99%